Discovery of a novel human lactate dehydrogenase A (LDHA) inhibitor as an anti-proliferation agent against MIA PaCa-2 pancreatic cancer cells. Issue 28 (29th February 2016) - Sun, Yunpeng; Tao, Chonglin; Yu, Fuxiang; Yang, Wenjun; Shan, Yunfeng; Yu, Zhengping; Shi, Hongqi; Zhou, Mengtao; Zhang, Qiyu; Wu, Huanhuan
Abstract : A potent LDHA inhibitor with anti-proliferation activity against MIA PaCa-2 cancer cells was first time reported. Abstract : LDHA has recently emerged as an attractive target for cancer therapy. Herein, we present the discovery of a potent LDHA inhibitor 12, which has good inhibitory activity to LDHA (IC50 = 1.50 μM). Moreover, the inhibitor 12 strongly inhibits the proliferation of MIA PaCa-2 pancreatic cancer cells (EC50 = 3.16 μM), suggesting it could serve as a promising candidate for further investigation.